Geographic Information System-Based Spatial Analysis of Agricultural Land Suitability in Yogyakarta - Harini Rika; Bowo Susilo; Emilya Nurjani (Faculty of Geography, Universitas Gadjah Mada, 2015)
Agricultural sector is the main economic activity of the society and also the source of people economy strengthening. The purpose of this study was to determine the priority direction of the development of the agricultural sector, mainly to determine the most appropriate types of commodities for each land unit that serve as local agricultural base. AHP method was integrated with GIS technique to analyze as well as to create land suitability maps for food crops. The results showed that 25.4 percent of lands in Yogyakarta is highly suitable for rice, while only 16 and 2 percent, respectively, is suitable for groundnut and corn. The limiting factors to the land suitability for these three commodities were plant roots condition, nutrients availability, nutrient retention, and soil condition. Suitable lands for rice, groundnut and corn were distributed at Ledok Wonosari, Middle Slope of Merapi, Lower Slope of Merapi and Batur Agung